Effects of Breccias and Round Gravels on Steep Cut Slope Runoff and Sediment Yield Under Simulated Rainfall - Luo Jing; Pei Xiangjun; Li Junhao; Cao Longxi; Shan Shihan; Huang Yingping (Shuitu baochi tongbao)
[Objective] The effects of breccias and round gravels on steep cut slope infiltration, runoff, sediment yield, and hydrodynamic characteristics were analyzed in order to provide a theoretical basis for a soil erosion prediction model and soil conservation on a steep cut slope on the Qinghai-Tibet Plateau. [Methods] Based on the shape and material composition of a steep cut slope and on climatic characteristics along the Pai-Mo road, the cut slope runoff and sediment yield process was observed by using indoor simulated rainfall experiments. The experimental conditions were 50° slope, 120 mm/h rainfall intensity, different gravel contents (30%, 40%, 50%), and different gravel roundness (pebble, breccia). [Results] The average infiltration rate for the pebble slope was higher than for the breccia slope. The average runoff rate for the pebble slope was lower than for the breccia slope. The initial runoff time for the pebble slope was significantly later than for the breccia slope. The water flow state and pattern for both slopes were laminar and jet, respectively. Although the runoff shear force and Reynolds number for the pebble slope was slightly smaller than for the breccia slope, the Froude number and the average flow velocity for the pebble slope were larger than for the breccia slope. Therefore, the ability of runoff to carry sediment was greater for the pebble slope. The sediment yield rate for the pebble slope was double the rate observed for the breccia slope, and the total sediment yield for the pebble slope was about 20% higher than for the breccia slope. [Conclusion] Because pebbles do not fit closely together in the soil, they are more likely to cause turbulence under heavy rainfall, causing small annular rills to form centered on the pebbles scattered all over the pebble slope. The rill density and total sediment yield will be greater for a steep cut slope underlain by alluvial deposits than for a steep cut slope underlain by colluvial deposits.